Pendampingan Ibu Menyusui Pada Masa Pandemi COVID-19 Guna Menjaga Ketahanan Keluarga - Rahayu Widaryanti (Perwakilan BKKBN Daerah Istimewa Yogyakarta, 2021)
One of the sectors affected by COVID-19 pandemic is family resilience. One way to maintain family resilience is by continuing to breastfeed during a pandemic. nursing mothers also have to maintain their psychological condition to maintain breast milk production. One way to maintain the continuity of the breastfeeding process without obstacles, is by assisting a breastfeeding counselor. This study aims to increase the knowledge of breastfeeding mothers about lactation management during the COVID-19 pandemic to maintain family resilience. This research using a quantitative approach, with a quasi-experimental design without a control group. The sample in this study was 40 breastfeeding mothers who had breastfeeding problems. Mentoring for breastfeeding mothers was carried out in April-June 2020. Data analysis used the Wilcoxon signed-ranks test. Based on the results of the calculation of the Wilcoxon signed-ranks test, it was found that the median pre-test and post-test value increased by 22 points, so that assistance to breastfeeding mothers during the pandemic had increased knowledge about management. lactation as much as 22 points. With the increased knowledge of mothers, it is hoped that mothers will continue to breastfeed in all conditions because breastfeeding the family's resilience can be maintained to achieve a prosperous family.